Multi-layered alert filtration and feedback cycle using Brahms model - Ghaffar, Abid; Wahiddin, Mohamed Ridza; Shaikh, Asadullah; Ahmad, Akhlaq (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Customer service improvement is directly related with organizational standards and productivity. Employees' activities have certain objectives to be followed but sometimes outcomes are different than expected. Human error while performing regular job activities cause sufficient losses and difficult to address. Management faces real challenges while dealing with employee related issues and sometimes becomes unproductive. We propose Brahms Model with multi layered alert filtration and feedback cycle which would address the human error in the system and generate the filtered alerts in the form of sms or by emails. This is especially useful for Human-Computer Interfacing (HCI) Scenarios. Controlling human error and addressing real issues may protect any institution from severe damage and losses. Efficiency of a customer service department can be improved and maximized by multi-layered alert filtration system using Brahms Model.